КРИСТАЛІЧНА СТРУКТУРА НОВОГО СИЛИЦИДУ Lu3Ni11,74(2)Si4 - Belan, Bohdana; Manyako, Mykola; Dzevenko, Mariya; Kowalska, Dorota; Gladyshevskii, Roman (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2020)
The new ternary silicide Lu3Ni11.74(2)Si4 was synthesized from the elements by arc-melting and its crystal structure was determined by the single-crystal X-ray diffraction. The compound crystallizes in the Sc3Ni11Ge4-type: Pearson symbol hP37.2, space group P63/mmc (No. 194), a = 8.0985(16), c = 8.550(2) Å, Z = 2; R = 0.0244, wR = 0.0430 for 244 reflections. The silicide Lu3Ni11.74(2)Si4 is new member of the EuMg5.2-type structure family.